2004
DOI: 10.3177/jnsv.50.144
|View full text |Cite
|
Sign up to set email alerts
|

Expressional Changes of Neuropeptide Y and Cholecystokinin in the Arcuate and Paraventricular Nuclei after Capsaicin Administration

Abstract: SummaryDespite its toxicity, a great deal of attention has been paid to the anorexic effect of capsaicin in the treatment of obesity-related neurotransmitters/neuromodulators . To determine if capsaicin has any effects on the orexigenic or anorexigenic peptides , the neu ropeptide Y (NPY) and cholecystokinin (CCK)-imunoreactivities were demonstrated in the rat hypothalamus by immunohistochemistry after capsaicin administration . There was a significantly lower concentration of NPY immunopositive cells in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The reduced NPY immunoreactivity in the LH and PVN, but not the ARC, after treatment with PD-type saponins supported a result that was similar to our previous study ; that is, PD-type saponins may inhibit the release of NPY or its transport to the PVN, rather than NPY synthesis in the ARC. Lee et al (2004) have reported the anorexic effect of capsaicin for the treatment of the obesity-related neurotransmitters/neuromodulators, NPY and CCK. There was a significantly lower NPY immunoreactivity in the ARC and PVN of the capsaicintreated rats compared with the control rats.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced NPY immunoreactivity in the LH and PVN, but not the ARC, after treatment with PD-type saponins supported a result that was similar to our previous study ; that is, PD-type saponins may inhibit the release of NPY or its transport to the PVN, rather than NPY synthesis in the ARC. Lee et al (2004) have reported the anorexic effect of capsaicin for the treatment of the obesity-related neurotransmitters/neuromodulators, NPY and CCK. There was a significantly lower NPY immunoreactivity in the ARC and PVN of the capsaicintreated rats compared with the control rats.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (20) found a significantly lower concentration of NPY-immunopositive cells in the arcuate and paraventricular nuclei in capsaicin-treated rats. Therefore, it is plausible that increased response to high-dose GLP-1 is mediated by a shift in the balance between orexogenic and anorexogenic hypothalamic peptide expression.…”
Section: Table 2 Numbers Of C-fos-immunoreactive Neuronal Nuclei In mentioning
confidence: 99%
“…A previous study showed that the administration of capsaicin decreased the expression of neuropeptide Y (NPY) and increased the expression of cholecystokinin in the rat hypothalamus [17]. They suggested that capsaicin may function to control food intake and obesity.…”
Section: Discussionmentioning
confidence: 99%